2015
DOI: 10.1177/0954407015586706
|View full text |Cite
|
Sign up to set email alerts
|

Research on a pneumatic hybrid engine with regenerative braking and compressed-air-assisted cranking

Abstract: With the aim of improving the energy efficiency of conventional vehicles, this paper proposes a pneumatic hybrid engine concept, which features regenerative braking and compressed-air-assisted cranking functions. In the regenerative braking mode, the engine works as a two-stroke compressor and converts the kinematic energy of the vehicle into compressed air. In the two-stroke air motor mode, a throttle valve in the intake manifold is used to block the ambient air, and an electropneumatic solenoid valve is empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is a simplified type-I RV mechanism with a vane slot cut into the cylinder in replacement of the bush component. 3 12.0…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a simplified type-I RV mechanism with a vane slot cut into the cylinder in replacement of the bush component. 3 12.0…”
Section: Methodsmentioning
confidence: 99%
“…Compressed air can be used to power pneumatic engines, otherwise known as air expanders, and essentially function as a clean energy source. It requires no electrical power input and has been proposed as an alternative power source for hybrid vehicles in which it is employed in conjunction with an internal combustion engine, replacing the electric motor in conventional hybrid vehicles [1][2][3]. Such hybrids can improve thermal efficiency by utilizing waste heat from the engine and extending the operating range of such vehicles when compared to electrical hybrids [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…An air injection boosting system is installed on a 6-cylinder diesel engine. The air tank is used to store the compressed air generated from recovering the engine brake energy as described in the previous work [40]. During the regeneration of engine brake energy, the engine is operated as an air compressor, generating compressed air and pump to the air tank through the pipe shown as the red line in Fig.…”
Section: Description Of the Hybrid Pneumatic Combustion Enginementioning
confidence: 99%
“…The simulation showed that the fuel mass consumed during the NEDC cycle was 677 g for a standard vehicle and 631.2 g for a hybrid pneumatic vehicle, indicating a fuel saving effect of 6.8%. Wang et al [26] conducted the simulation study of a hybrid pneumatic engine under urban driving-cycle, showing that the fuel consumption of a light-duty vehicle equipped with a hybrid pneumatic engine can be reduced by 8%. In addition to those mentioned above, a few numerical studies were also reported on the fuel-saving effect of hybrid pneumatic engine in different 5 applications [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the fuel economy generated by HPE was 10%~26% under different wind power conditions. Wang et al [27] conducted a simulation study on a HPE to regenerate the braking energy and urban driving-cycle simulation results pointed out the fuel consumption of a light-duty vehicle with pneumatic hybrid system can be reduced by 8 %. A two-stage expansion air engine, which includes one small and one large cylinder to conduct two-stage in series has been proposed and investigated by Liu et al [28].…”
Section: Introductionmentioning
confidence: 99%